Anatomy-based treatment strategy for abdominal and retroperitoneal cystic lymphatic malformations in children - Diehtiarova, D. S. (General Surgery, 2022)
Lymphatic malformations (LMs) are rare congenital benign malformations of the lymphatic system, consisting of fluid‑filled cysts or channels with unusual growth. The low incidence of LMs leads to a challenging differential diagnosis and a complicated choice of further treatment strategies. In this study, we analyzed our experience in the treatment of abdominal and retroperitoneal cystic LMs and proposed an anatomy‑based treatment strategy that could improve the treatment outcomes. Objective — to prove that the anatomical localization of LM influences treatment effectiveness and should be taken into account when making treatment decisions. Materials and methods. Out of 240 pediatric patients who underwent treatment for cystic LMs at a single center from December 2012 to December 2020, 43 (19.1 %) were diagnosed with abdominal and retroperitoneal LMs. The follow‑up period was 3.50 ± 2.16 years. Results. Surgical resection of abdominal LMs without evident connection with cisterna chyli does not lead to a recurrence. Sclerotherapy is the best treatment option for retroperitoneal LMs. Diffuse mesentery affection can be successfully treated by sirolimus systemic therapy. According to a logistic regression model, initial choice of LM treatment without considering anatomical localization influences the risks of LM treatment failure (p = 0.000503). All patients in our study group received the following treatments: laparoscopic resections (n = 10, 23.2 %), videoassisted resections (n = 11, 25.5 %), laparotomy resections (n = 9, 20.9 %), sclerotherapy (n = 4, 9.3 %), sclerotherapy and surgery combination (n = 1, 2.3 %), sirolimus systemic therapy (n = 2, 4.6 %), and splenectomy (n = 1, 2.3 %). Six (13.4 %) patients are under dynamic observation. The recommended technique for treating abdominal LMs produced excellent outcomes in 35 (81.4 %) patients, good outcomes in 5 (11.6 %) patients, satisfactory outcomes in 2 (4.7 %) patients, and unsatisfactory outcomes in 1 (2.3 %) patient. Conclusions. Treatment strategies for abdominal and retroperitoneal LMs should be based on their anatomical localization. Retroperitoneal localization indicates a high risk of surgical treatment failure (p = 0.0006).